The mediating role of physical activity, morning wake-up time, and sleep-inducing medication use in the relationship between age and depression: a path analysis of a large kurdish cohort study in Iran - Fahimeh Alsadat Hosseini; Samaneh Bagherian; Cristina Cañete-Massé; Mehdi Moradinazar; Farid Najafi (BMC Public Health)
Abstract Background Depression is a common and debilitating psychiatric disorder worldwide. Recognizing the relationships between depression-related factors can play a significant role in depression management. However, no study has yet used path analysis to examine the mediating role of physical activity, morning wake-up time, and sleep-inducing medication in the relationship between age and depression. Methods This path analysis study utilized data from the baseline phase of the Ravansar non-communicable disease cohort study. This study was conducted on people aged 35 to 65 years using sociodemographic, clinical, and the PERSIAN cohort’s standard physical activity questionnaires. These analyses were done using SPSS (version 22) and MPLUS (version 8.3). Path analysis was applied to evaluate the direct, indirect, and total effects of age on depression. Results The results indicated that increasing age was associated with an increase in depression through a decrease in physical activity and an increase in sleep-inducing medication use. In addition, an increase in age was significantly related to a reduced incidence of depression via an earlier morning wake-up time. Discussion We found evidence for a mediational effect of age on depression, as the biopsychosocial model of mental illness implies. The findings of this study can add to the existing body of knowledge on depression management and help clarify the mechanisms of the effect of age on depression.